Brain Stem Hypertensive Encephalopathy Evaluated by Line Scan Diffusion-Weighted Imaging - Nagata, Motonori; Maeda, Masayuki; Tsukahara, Hirokazu; Maier, Stephan E.; Takeda, Ken (American Journal of Neuroradiology, 2004)
Summary: Hypertensive encephalopathy rarely presents with predominant involvement of the brain stem and relative sparing of the supratentorial regions. We describe the MR imaging features in a patient with reversible brain stem hypertensive encephalopathy. Extensive hyperintensity was predominantly seen in brain stem regions on fluid-attenuated inversion-recovery and T2-weighted images. These lesions showed an increased apparent diffusion coefficient with the use of line scan diffusion-weighted imaging. The clinical findings and MR imaging abnormalities resolved with control of hypertension.